1992
DOI: 10.1016/0885-3924(92)90077-u
|View full text |Cite
|
Sign up to set email alerts
|

Phenytoin as a coanalgesic in cancer pain

Abstract: The efficacy of phenytoin (PHT), buprenorphine (Bu), and Bu+PHT for the relief of cancer pain of various etiologies was evaluated in a randomized, double-blind study of 3 groups, each comprised of 25 patients. Treatment duration was 1 month. PHT (100 mg by mouth twice daily) provided greater than 50% pain relief to 18 patients (72%) and greater than 75% relief to 4 (16%). Bu (0.2 mg sublingually twice daily) gave 21 patients (84%) greater than 50% relief and 15 patients (60%) greater than 75% relief. Of the Bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
38
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 5 publications
0
38
0
Order By: Relevance
“…Pregabalin (Pfizer Pharmaceuticals) is a new anticonvulsant with a mechanism identical to that of gabapentin and strong evidence of analgesic efficacy [68]; this drug will soon be avail- [52]. The classic indication for carbamazepine is trigeminal neuralgia [52], and the use of phenytoin in cancer pain has been described [71]. Due to their frequent side effects (sedation, dizziness, nausea, unsteadiness) and potential for drug-drug interactions, the use of these drugs has declined with the introduction of the newer analgesic anticonvulsants.…”
Section: Anticonvulsant Drugsmentioning
confidence: 99%
“…Pregabalin (Pfizer Pharmaceuticals) is a new anticonvulsant with a mechanism identical to that of gabapentin and strong evidence of analgesic efficacy [68]; this drug will soon be avail- [52]. The classic indication for carbamazepine is trigeminal neuralgia [52], and the use of phenytoin in cancer pain has been described [71]. Due to their frequent side effects (sedation, dizziness, nausea, unsteadiness) and potential for drug-drug interactions, the use of these drugs has declined with the introduction of the newer analgesic anticonvulsants.…”
Section: Anticonvulsant Drugsmentioning
confidence: 99%
“…In a cancer pain trial, phenytoin co-administration led to reduced opioid requirements and also gave better pain relief. 66 Various other lines of animal and human evidence suggest further that gabapentin, 67,68 lamotrigine, 37 writing. All of these trials, as evaluated by the author (I.G.…”
mentioning
confidence: 99%
“…With chronic, stable neuropathic pain, oral anticonvulsant drugs can be titrated to an effective dose. Yajnik et al 6 have reported > 50% pain relief in 72% patients with a phenytoin dose of 100mg BD for 1 month duration in a randomized double blind study. In this case we have used a higher dose of phenytoin looking at the severe nature of pain and favorable side effect profile of the drug.…”
Section: Discussionmentioning
confidence: 99%